Attending a one-to-one child-centered movement therapy program improves multiple outcomes among children with neurodevelopmental disabilities: an exploratory prospective cohort study - Gitimoghaddam, Mojgan; McKellin, William H.; Olsen, Lise; Miller, Anton R.; Symington, Vivien; Collet, Jean-Paul (Frontiers in Pediatrics, 2025)
IntroductionChildren with neurodevelopmental and/or intellectual disabilities/disorders (NDID) often face barriers that limit their participation in typical school and community activities alongside their peers. Adapted, community-based physical activity programs may help bridge this gap by offering safe and engaging environments that promote integration, socialization, and learning. This study aimed to evaluate the potential effects of the Empowering Steps Movement Therapy (ESMT™) one-to-one personalized physical activity program on children and youth with NDID.MethodA prospective cohort study was conducted to collect information regarding the changes in participants’ motor skills (measured by BOT-2-SF), social and leisure adaptive skills (measured by ABAS-II), community and home participation (measured by PEM-CY), and quality of life (measured by KIDSCREEN-27). Forty-two children and youth with NDID attending the ESMT™ program were followed for 12 months with follow-up every 3 months. A linear mixed-effects (LME) model was used to analyze longitudinal changes, as well as studying the influence of children's and families' baseline characteristics on the outcomes.ResultsFor motor skills, children showed a small but consistent positive trend in standardized motor skills (BOT-2-SF) over time, averaging 0.17 points per month (95% CI: −0.01 to 0.34; p = 0.06), with a slightly higher gain among autistic children (0.20 points; 95% CI: −0.03 to 0.43; p = 0.08). Positive trends were also observed in home and community participation. However, improvements were minimal for social adaptive skills, and a slight decline was noted in leisure adaptive skills and quality of life. Several potential confounders including parental education, socioeconomic status, and participation in other community-based programs were examined, indicating that some may play a significant role. Notably, the type of underlying condition contributing to neurodevelopmental disability appeared to be an important effect modifier for both motor skills and social adaptive skills.ConclusionDespite the small sample size, this study suggests that individualized, one-to-one physical activity programs which provide individualized scaffolding tailored to each child's unique needs, may yield meaningful improvements across multiple domains in children with NDID. Larger studies are warranted to validate these findings and further support the adoption of personalized, socially engaging approaches in therapeutic physical activity settings.